LOGISTICS AND LEVELS OF SERVICES IN COMPANIES - Antonio Miqueluti, Rhuan; Sobral, Fábio Luís (Revista Interface Tecnológica, 2021)
Logistics and service levels are designed to organize processes and speed up productivity, quality and time. So, this paper is a study on logistics and service levels in the area. The main objective is to understand that logistics is fundamental for any company, since if an organization has excellent products, but does not deliver on Overtime can interfere with the feedback that the customer will pass on the company. The methodologies that make up this article are bibliographic, descriptive and exploratory and through these research techniques can be seen the importance of service levels in logistics and the indicators used to evaluate them. It is concluded that the company that wants to stay active and ahead of the competitive market, needs to invest and consequently improve the logistic levels of the organization.
Keywords: Logistics; Levels of service; Performance indicators; Feedback; Customers